SOME OBSERVATIONS ON THE BIOLOGY OF COILIA BORNEENSIS (BLKR) - Varghese, T J (Indian Journal of Fisheries, 2011)
Coilia bomeensis, locally known as "Amadi," is a medium-sized clupeoid very common in the estuaries of West Bengal. Day (1878) has recorded the species from Madras, Burma and the Malay Archipelago. The fish is more abundant in the middle stretch of the estuarine system than in the upper and lower zones. Bag-net (Beenjal, Behundijal or Thorjal) is the main gear by which C. bomeensis is caught, though it is also taken along with other fishes in the catches of barrier-nets (Chorpatajal) and shore-seines (Berjal).